The photographers of the Broquier family, with a light of their own - Agustín Lacruz, Carmen (Revista General de Información y Documentación, 2023)
Pablo Broquier was a French-born photographer who ran prestigious establishments in Bilbao and Irun and founded photographic plate companies in Amorebieta (Biscay) and Madrid, from the end of the last decade of the 19th century until the end of the 1920s. After his death in 1931, the women of his family made photography their professional activity and livelihood. They opened a photographic studio in Arnedo (La Rioja) between 1927 and 1930 and then settled in Tarazona (Zaragoza) from 1931 to 1957. They worked for almost three decades under the trade name of Fotografía Colón. Hermanos Broquier y Foto Colón, making studio, outdoor and ambulance photography and cultivating portraits, graphic reports of parties, celebrations and events and graphic collaborations with the newspapers of the time. This article studies the professional career and graphic work of the photographers Paula Broquier Cottafava and her daughters Elena, Eugenia and Inés Broquier Gautier and their contribution to the development of the photographic medium in Spain in the first half of the 20th century. To this end, we have reviewed oral, bibliographic, archival and newspaper sources that have provided unpublished data of interest, and we have also inventoried and analyzed the photographic work available, which provide a valuable graphic record of the people and their way of life during the Second Republic, the Civil War and the dictatorship.
Keywords: Female photographers; Photographic documentation; Pablo Broquier Gautier (Lorgues, 1859 – Tarazona, 1931); Paula Gautier Cottafava (Savona, 1880 – Rueil Malmaison, 1977); Carlos Broquier Gautier (Amorebieta, 1905 – Funes, 1980); Elena Broquier Gautier (Amorebieta, 1906 – Barcelona, 1986); Eugenia Broquier Gautier (Irún, 1918 – Tudela, 1985); Inés Broquier Gautier (Irún, 1918 – Neuilly-sur-Seine, 2000); Tarazona (Zaragoza); Arnedo (La Rioja)